Penentuan Struktur Modal untuk Mencapai Biaya Modal Minimum dan Pengaruhnya terhadap Nilai Perusahaan - Hadisoebroto, Andreas E. (Fakutas Ekonomi Unika Widya Mandala Surabaya, 2004)
Company grows together with the growth of its working capital and fixed assets. To be able to show significant growth, company needs capital which managements always try to provide in the minimum cost. The problem is how the management maintains optimum capital structure. Capital structure should cost as little as possible because capital is the only funding resource. The objective of this article has is study management policy in defining capital structure, using Modigliani and Miller propositions. It is expected that the effect of capital structure to cost capital and firm's value can be proved.